Factors contributing to the distress, concerns, and needs of UK Neuroscience health care workers during the COVID‐19 pandemic. (16th July 2020) - Cipolotti, Lisa; Chan, Edgar; Murphy, Patrick; van Harskamp, Natasja; Foley, Jennifer A.
Abstract : COVID‐19 research from China suggests health care workers are at risk of distress, have specific concerns, and need support. It remains unknown whether findings are applicable to UK health care staff and whether psychological support based on generic approaches is effective. We administered an online survey at a leading neuroscience hospital in the UK to examine how individual staff characteristics contribute to distress, concerns, and interventions most valued during the COVID‐19 pandemic. We found a high incidence of distress, particularly in females and staff with previous mental health history. Concerns fell into three factors: 'risk of infection', 'work challenges', and 'social change', and were affected by professional role and contact with COVID‐19 patients. These three factors predicted distress. Psychological support and clear updates were deemed most useful, with specific needs affected by age, professional role, and contact with COVID‐19 patients. This is the first documentation of a high incidence of psychological distress predicted by three types of concerns in health care workers of a neuroscience hospital. Distress, concerns, and interventions most valued were all affected by individual staff characteristics. These findings highlight the importance of providing stratified, one to one support interventions, tailored to professional group, and background, rather than more generic approaches. Practitioner points: The COVID‐19 pandemic has resulted in a high incidence of psychological distress in UK health care staff. Distress, concerns, and interventions most valued are influenced by individual staff characteristics. Stratified, one‐to‐one support interventions, tailored to professional group, and background, rather than more generic approaches for stress reduction and resilience, are crucial.